Surgical Clips in Breast-conserving Surgery: Do they Represent the Tumor Bed Accurately? - ÖZGEN, ZERRİN (BENTHAM SCIENCE PUBL LTD, 2019)
Introduction: Radiotherapy after Breast-Conserving Surgery (BCS) is a standard treatment for breast cancer. Currently, surgical clips are used to determine the tumour bed before radiotherapy planning. This study aimed to evaluate the migration of these clips on mammograms. Methods: The study was conducted on 121 females who were treated with radiotherapy after BCS at their first radiologic control examination 6 months after the end of treatment. MLO and CC views of all cases were evaluated regarding the clips. The distance between the surgical scar centre and the centre of the area covered by the clips was measured on both MLO and CC projections and recorded separately. This distance was determined as the clip displacement. A displacement <= 10 mm was recorded as no displacement. Results: The clips were out of the images and were not evaluated in 45 cases (37.2%) on CC and in 9 cases (7.4%) on MLO projections. There were no clip displacements in 37 (30.6%) cases on CC and in 43 (35.5%) cases on MLO views. The amount of displacement ranged from 11 to 56 mm with a mean of 24.38 mm on CC views, while on MLO projections, displacement ranged from 11 to 66 mm with a mean of 24.42 mm. Conclusion: A clip displacement of greater than 10 mm was found in 64.5% of cases on MLO views. Therefore, we believe that the reliability of these clips for accurate delineation of the tumour bed in radiotherapy planning is controversial and other methods must be added.
Keywords: Surgical clips; breast-conserving therapy; localization; tumour bed; radiotherapy; breast cancer; 20-YEAR FOLLOW-UP; RADIOTHERAPY; CT; IRRADIATION; MASTECTOMY; CANCER; BOOST; LUMPECTOMY; THERAPY